The Effect of Service Quality and Patient Satisfaction on Patient Loyalty Mediated by Patient Trust at Byor Skin Clinic - Jessica Lepianda; Wani Devita Gunardi; Fushen Fushen (PT. Anagata Sembagi Education, 2024)
Nowadays, women in Indonesia are very fond of the beauty and smoothness of the skin of Korean artists, along with the increasing trend of drama and KPOP in Indonesia, many are competing to do beauty treatments to be able to maintain their appearance and have white, clean, bright, glowing skin or what is currently often called clear skin. The increasing awareness of self-beauty treatments are in line with the beauty industry in Indonesia which also continues to grow, it can be seen from the increasing number of people who visit and perform treatments at beauty clinics and the increasing number of beauty clinics that we can find. Data were obtained through questionnaires distributed randomly. The analysis technique was SEM and using AMOS software version 23. Based on the analysis results, it was found that out of 7 hypotheses, there was 1 hypothesis that rejected, and other 6 hypotheses were accepted. The service quality has no positive effect to the patient loyalty, the patient satisfaction has positive effect to patient loyalty, patient trust has positive effect to patient loyalty, service quality has positive effect to patient trust, patient satisfaction has a positive effect to patient trust, patient trust has positive effect mediate service quality with patient loyalty, and the patient trust also has positive effect mediate patient satisfaction with patient loyalty.